The role of parent relations in self-harmful behavior and suicidal ideation among adolescents - Maria Eupprasia Piliter Tuto Unarajan; Titus Angga Restuaji; Agus Basuki (Insight: Jurnal Ilmiah Psikologi, 2024)
Parents have to nurture a good relationship with adolescents to avert self-harmful behavior and suicidal ideation, which increasingly happen. This research aims to understand the effect of parent-child relationships on self-harm behavior and suicidal ideation. The subjects of this study are 1063 junior high school (JHS) and senior high school (SHS) students in Tarakanita Foundation (TF). This research is a double linear regression based on the t-test and f-test, which use the t-table and f-table. This research shows a significant effect between parent-child relationships and self-harmful behavior. A good, safe, and loving relationship with parents can prevent adolescents from self-harmful behavior and suicidal ideation. On the other hand, a disharmonious relationship between parents and adolescents, such as an experience of violence, feeling depressed, and a traumatic experience in the family, is why adolescents harm themselves and have suicidal ideation. Based on this study, parents are expected to nurture a good relationship with their children. The benefit of research is that it provides parents with a good understanding of the dangers of self-harm behavior and how to handle it appropriately by parents or professionals who can help parents deal with self-harm behavior in their adolescence. This research is also useful as the information that the importance of building strong and healthy relationships with children is becoming increasingly important; thus, appropriate behavior. Keyword: Parent relation; self-harm; suicidal ideation; adolescents.